Harmoni Ekologis dalam Petuah Adat Sikka dan Lamalera: Pedoman Hidup di Tengah Tantangan Modern - Christian Wildeciano Jogo; Marselinus Kalang Lelaona; Kasimirus Rape Baluk (Fakultas Teologi, Universitas Sanata Dharma, 2026)
This research analyzes the noble values of the Sikka and Lamalera communities contained within the customary advice,